Effects of microscopic testa color and morphologyon the water uptake ability and drought tolerance of germination-stage rapeseed (Brassica napus L.). Issue 2 (20th December 2021) - He Zhu, Zong; Sami, Abdul; Peng Chen, Zhi; Fatima, Maliha; Yin Zheng, Wen; Xu, Qing Qing; Hang Lei, Yu; Zhi Jin, Xue; Zhang, Hong; Li, Yong; Yu, Yan; Zhou, Ke Jin
ABSTRACT: Drought is one of the most important abiotic stressors that affect crop yield. Therefore, the aim of the present study was to investigate correlations between germination-stage drought tolerance and the microscopic testa (i.e., seed coat) characteristics (color and papilla morphology) and imbibition abilities of 35 rapeseed ( Brassica napus L.) accessions. After 2 h imbibition, seed water uptake (fresh weight increase) was significantly positively correlated with testa hue ( H HSB ), brightness ( B HSB, ), blue ( B RGB ), and lightness ( L *), with correlation coefficients of 0.38, 0.34, 0.53, and 0.36, respectively, and significantly negatively correlated with saturation ( S HSB ), greenness-redness ( a *), blueness-yellowness ( b *), magenta ( M ), and yellow components ( Y ), with correlation coefficients of −0.53, −0.40, −0.53, −0.39, and −0.55, respectively. Furthermore, 5-h seed water uptake was significantly positively correlated with number of papillae (No.P), mean papillae area (APA), the papillae area ratio (PAR), gray value of red channel of papillae, with correlation coefficients of 33, 0.36, 0.43, and 0.43, respectively. Under drought conditions, genotypes with more rapid water absorption exhibited higher germination rates and stronger drought tolerance, and the germination rate and drought tolerance of black-seeded accessions were highest, followed by red-seeded accessions and then yellow-seeded accessions, which exhibited the lowest germination rate and drought tolerance. Germination rate was significantly negatively correlated with B RGB, H HSB, L*, D g, and D b and significantly positively correlated with S HSB and Y, regardless of drought conditions. At the germination stage, D b TP was negatively correlated with drought tolerance.